Determination of effective diffusion coefficient of immobilized Baker's yeast invertase in various concentration of PVA-alginate matrix - Mohd. Zain, N. A.; Suhaimi, M. S.; Idris, Ani (Faculty of Engineering, International Islamic University Malaysia, 2007)
Baker's yeast invertase is immobilized in PVA-alginate matrix using an improved method. PVA beads were prepared by adding calcium alginate to improve its stability, mechanical and chemical properties. Boric acid was used as the cross-linking agent and additional chemicals consisting of 10% boric acid and sodium sulphate solution was used as a treatment solution to harden the PVA-alginate beads. The determination of the effective diffusion of PVA-alginate matrix the vital step in optimizing the preparation of immobilized and water-soluble biocatalyst. In this study the two-level full factorial design was used to investigate the effect of PVA and boric acid concentrations and diffusions coefficient. Diffusion coefficient (De) is one of the factors that significantly affect the mass transport within the immobilization matrix. De value varies for each concentration of PVA and boric acid. The result concluded that both factors significantly affect the De. A maximum De value of 5.0141 x 10(-5) cm2s-1 was obtained at boric acid and PVA concentraion of 7w/v and 10.5 w/v respectively.